Servo Control Education Tool for Industrial Applications - Işık, M. F.; Coşkun, İ. (Elektronika ir Elektrotechnika, 2010)
In this study, a training set consisting of servo motors is designed to assist development of the students, especially who are in electrical, electronics and mechanical engineering, in industrial field. For this training set; three AC servo motors and one DC servo motor are used and four-axis control mechanism is generated. In order to control servo motors a special driving circuit is developed through which position and speed is controlled. These controls can be managed either via operating panel (touch panel) or via computer depending on user’s purpose. In addition, a local network based training software is developed, which involves theoretical information regarding servo motors and allows testing opportunity and observing animations. Thus, a practical, functional and also economical training set allowing students both to learn and to perform many applications that they might be introduced with industrial field is developed.